2010
DOI: 10.1111/j.1521-0391.2010.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Unconventional Treatments for Stress among Methadone-Maintained Patients: Treatment Willingness and Perceived Efficacy

Abstract: We surveyed 150 methadone maintenance treatment (MMT) program patients about willingness to use, and perceived efficacy of, conventional and unconventional nonpharmacological stress-related treatments. Although levels of treatment willingness and perceived efficacy for both conventional and unconventional treatments were high, ratings for conventional interventions were, on average, significantly higher than those for unconventional ones. Dimensions of psychiatric distress—but not demographic or MMT characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Participants who met recommended levels of physical activity in the past week had significantly lower levels of depression compared to participants that did not. Complementary to these findings, another study 29 reported that methadone-maintained patients were willing to consider physical exercise as a treatment for stress, with reasonably high perceived efficacy of exercise.…”
Section: Substance Abuse: Research and Treatmentmentioning
confidence: 75%
“…Participants who met recommended levels of physical activity in the past week had significantly lower levels of depression compared to participants that did not. Complementary to these findings, another study 29 reported that methadone-maintained patients were willing to consider physical exercise as a treatment for stress, with reasonably high perceived efficacy of exercise.…”
Section: Substance Abuse: Research and Treatmentmentioning
confidence: 75%
“…Increased abstinence behavior and decreased cravings have likewise resulted from mindfulness or neurofeedback (biofeedback focused on electroencephalograms, EEG) training in substance abuse treatment (Kevin W Chen et al, 2013; Goldberg et al, 2014; Ross, 2013; Stasiewicz et al, 2013), including opioid addiction (Dehghani-Arani, Rostami, & Nadali, 2013). Higher anxiety or distress has recently been found to increase willingness and perceived treatment efficacy for group stress reduction therapy in MMT (Barry et al, 2011), thus increasing feasibility of incorporating this training into existing intensive outpatient programs. The ASI drug and psychological composite scores with identification of abnormal salivary CORT could be used as routine admission screening tools to identify individuals susceptible to premature discontinuation and stratify treatment interventions in MMT Assessing patient engagement and compliance again at three months may enable determination of interventional efficacy and predict ongoing retention or relapse-risk.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas we previously reported on a) the prevalence of pain and associated substance use and psychiatric correlates, b) prior pain treatment utilization, and c) perceptions of individual psychosocial interventions among the study sample, we did not report on findings related to willingness to use stress-reducing conventional and unconventional group treatments or the perceived efficacy of such interventions (Barry et al, 2009a; Barry et al, 2009b; Barry et al, in press-a). The primary goal of this needs assessment study was to examine treatment willingness and perceived efficacy of nonpharmacological conventional and unconventional group treatments for managing stress.…”
Section: Introductionmentioning
confidence: 70%